Effects of brace on pedobarographic parameters in individuals with adolescent idiopathic scoliosis - Altun, Yağmur; Dilek, Burcu; Yakut, Yavuz (My University, 2021)
Purpose: The aim of the study was to evaluate the immediate effects of brace on static, dynamic and stabilometric changes in individuals with Adolescent Idiopathic Scoliosis (AIS).Methods: Twenty-nine AIS individuals (24 girls; 5 boys) aged between 10-19 years and have moderate curve (20-45°) included into the study. Static, stabilometric and dynamic data of the individuals were recorded by the DIASU pedobarography device (Diasu Company, Rome, Italy 4024 sensor, 300 MHz frequency). Assessments were carried out on same individuals in-brace and without-brace conditions. All data were recorded with Milletrix software (Diagnostic Support, Rome, Italy) and transferred to computer system. Results: There were no differences between with in-brace and without-brace conditions on static and stabilometric values (p>0.05). However, it was found that braces affected dynamic values such as footstep length and foot acceleration on the left side (p<0.05). It was observed that these values decreased with using braces.Conclusion: Immediate effects of bracing could change dynamic pedobarographic variables such as acceleration and steplength. Regarding short-term effects of bracing on dynamic parameters, therapists and orthotists should consider thecompensatory effects of bracing through the rehabilitation.

Amaç: Çalışmanın amacı, adolesan idiopatik skolyozlu (AİS) bireylerde skolyoz ortezinin statik, dinamik ve stabilometrik değişimleri üzerine anlık etkilerini değerlendirmekti.Yöntem: Çalışmamıza 10-19 yaş aralığında ve orta derecede eğriliğe (20-45°) sahip olan 29 birey (24 kız, 5 erkek) dahil edildi. DIASU (Diasu Company, Rome, Italy 4024 sensor, 300 MHz frequency) pedobarografi cihazı ile bireylerin statik, stabilometrik ve dinamik verileri kaydedildi. Değerlendirmeler aynı bireylerde ortezil ve ortezsiz durumlarda gerçekleştirildi. Veriler Milletrix yazılımı (Diagnostic support, Rome, Italy) ile kayıt altına alındı ve bilgisayar sistemine aktarıldı. Bulgular: Ortezli ve ortezsiz durumda yapılan analizlerde statik ve stabilometrik değerler arasında değişiklik saptanmadı(p>0,05). Bununla birlikte, Ortezin sol ayak adım uzunluğu ve sol ayak ivme gibi dinamik değerleri etkilediği bulundu(p<0,05). Ortez kullanımıyla beraber bu değerlerde azalma görüldü.Sonuç: Skolyoz ortezinin anlık etkileri ivme ve adım uzunluğu gibi dinamik pedobarografik değerleri değiştirebilmektedir. Ortotist ve fizyoterapistlerin, skolyoz ortezinin dinamik parametreler üzerindeki kısa dönem etkilerini dikkate alarak, rehabilitasyon süresince ortezin kompansatuar etkilerini göz önünde bulundurmaları gerekmektedir.
Adolesan idiopatik skolyozlu bireylerde ortezin pedobarografik parametreler üzerine etkisi
Keywords: Braces; Scoliosis; Gait Analysis; Ortez; Skolyoz; Yürüme Analizi